Isolation and Identification of Osmophilic Yeast from unripe Jackfruit (Artocarpus heterophyllus Lamk.) - Nanik Suhartatik; Mimin Nurjanah; Kapti Rahayu Kuswanto (Indonesian Journal of Agricultural Research, 2018)
Osmophilic yeast are microbes that are able to live on media with high sugar concentrations. Some types of osmophilic yeast can break down organic compounds, for example, starch. This research was aimed to isolate and identify existing osmophilic yeast in unripe jackfruits. In this research, the unripe jackfruit was left rotting and 2.5 g of the sample were taken to be solved in 25 ml 0.85% NaCl and diluted. The GYP (glucose-yeast-peptone) agar medium with the glucose concentration of 30“50% was suitable for osmophilic yeast growth. Isolate purification was performed using the streaking method from single colony. Isolates were identified based on physiological and morphological characteristics. The physiological characterization were carried out by running sugar assimilation test on the tool kit API 20C AUX, while the morphological characterization was carried out by performing macroscopic and microscopic observations. Four isolates were assumed to be Candida lambica, 3 isolates were assumed to be Candida rugosa and two isolates were assumed to be Geotrichum candidum. It was found out that 44.4% of yeast in the unripe jackfruit were Candida lambica, 33.3% was Candida rugosa and 22.2% was Geotrichum candidum. Candida lambica was the most common osmophilic yeast found in the jackfruit.